2022
DOI: 10.1186/s13104-022-05957-w
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness and cardiometabolic health in omnivores and vegetarians: a cross-sectional pilot study

Abstract: Objective Arterial stiffness is a strong predictor of cardiovascular mortality, and often precedes elevations in blood pressure. This cross-sectional pilot study examined differences in arterial stiffness, blood pressure, cardiometabolic markers, anthropometric outcomes, and inflammation in vegetarians and matched omnivores. Participants were healthy, non-smoking adults (18–65 years old) adhering to either a vegetarian/vegan or omnivore diet. Omnivores were matched to vegetarians using broad bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Thus, preventing arterial stiffness seems reasonable in improving cardiovascular health. In the literature, various nutritional interventions regarding arterial stiffness have recently been widely discussed [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , …”
Section: The Impact Of Diet On Arterial Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, preventing arterial stiffness seems reasonable in improving cardiovascular health. In the literature, various nutritional interventions regarding arterial stiffness have recently been widely discussed [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , …”
Section: The Impact Of Diet On Arterial Stiffnessmentioning
confidence: 99%
“…The beneficial influence of a low-fat meat diet is seen mainly in studies analyzing the impact of diets typical for omnivores and vegetarians/vegans on arterial stiffness, for example, lower PWV (−8%) in healthy male vegetarians ( n = 44) compared to the omnivore control sample ( n = 44; 7.1 ± 0.8 and 7.7 ± 0.9 m/s, respectively) [ 90 ]. Similarly, the study of Mayra et al has shown a tendency for higher arterial stiffness in omnivores versus vegetarians (7.0 ± 1.5 and 6.8 ± 1.1 m/s, respectively; p = 0.073), mainly male omnivores ( p = 0.006 for the effect of gender and p = 0.294 for the effect of the eating pattern effect), suggesting that the beneficial effect of the vegetarian eating pattern may be limited in premenopausal women [ 91 ].…”
Section: The Impact Of Diet On Arterial Stiffnessmentioning
confidence: 99%
“…For atherosclerosis, the studies included a total of 227 and 247 healthy subjects for vegetarian and omnivorous diets, respectively (age range 24–60 years), and for arterial stiffness, the studies included a total of 253 and 259 healthy subjects for vegetarian and omnivorous diets, respectively (age range 20–70 years). Finally, six studies measured cf-PWv 26,27,29,31–33 as an index of arterial stiffness and seven studies measured c-IMT 24,25,27–31 as an index of atherosclerosis. Table 1 shows the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 10 studies [24][25][26][27][28][29][30][31][32][33] were included in the systematic review and seven in the meta-analysis [24][25][26][27]30,32,33 (Fig. 1).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Overall, intermittent fasting appears to reduce inflammation and oxidative stress, portending improvement in inflammatory phenotypes such as hypertension, obesity, insulin resistance, and hyperlipidemia. Despite this promising evidence, there remains a need for additional large RCTs to assess the long-term impact of IF on inflammation as it pertains to cardiovascular risk [65,66] .…”
Section: Intermittent Fastingmentioning
confidence: 99%